Book reviews - Rautaniemi, Matti; Sjö, Sofia (Approaching Religion, 2012)
The American Soul Rush: Esalen and the Rise of Spiritual Privilege by Marion Goldman is reviewed by Matti Rautaniemi.India: A Sacred Geography by Diana L. Eck is reviewed by Sofia Sjö.